A review on recent advancements in bioenergy production using microbial fuel cells. (February 2022) - Ramya, M.; Senthil Kumar, P.
Abstract: The generation of energy and its efficient use in industries and agriculture are critical to any country's growth. A country like India, which is still developing, faces a major challenge in terms of generating adequate electricity. With the current crisis and environmental concerns, the government must look past carbon-based energy sources and into long-term energy sources. Microbial fuel cells (MFCs) are a form of technology that can be used to both treat wastewater and generate electricity on a large scale. Researchers play a critical role in making this technology practical and effective enough to be implemented. However, since the charge of building microbial fuel cells is superior than the cost of fossil fuels, it is unlikely that power production will continually be aggressive with existing energy generation approaches. However, improvements in power densities and lower material expenses could render microbial fuel cells a viable option for energy making in the future. Following a thorough literature review, the analysis resumes the role of micro-organisms and substrates in the anode chamber. Microbial fuel cells are discussed in terms of their forms, materials, mechanism, and activity. This analysis discusses the various factors that influence microbial fuel cells, as well as contemporary challenges and applications in the development of sustainable electrical power. Graphical abstract: Image 1 Highlights: This review summarizes the current state of knowledge about microbial fuel cells. The elements that determine MFC design, materials, and performance were highlighted. The practical application of MFC energy output is described. Challenges that prevent the technology from being used in real-world applications are discussed. MFC technology provides a green alternative for low-cost energy generation.